Interstitial deletion of chromosome 13: prognosis and adult phenotype. Issue 8 (August 1991) - Dean, J C; Simpson, S; Couzin, D A; Stephen, G S
Abstract : A de novo interstitial deletion of chromosome 13 (46, XY, del(13)(pter----q14.3::q22.3----qter] is described in a 22 year old man with severe mental retardation, poor language development, low set ears, hypertelorism, broad nasal bridge, short hands and fingers, and a history of swallowing disorder in childhood with subsequent dyspepsia. The dysmorphic features did not become evident until later childhood, supporting the view that karyotyping should be performed routinely in all children with developmental delay.